When climate change is not psychologically distant – Factors influencing the acceptance of sustainable farming practices in the Mekong river Delta of Vietnam - Connor, Melanie; Guia, Annalyn H. de; Quilloy, Reianne; Hung Van Nguyen; Gummert, Martin; Sander, Björn Ole (Elsevier, 2020)
Rice farmers in the Mekong Delta are not only experiencing challenges due to climate change but are also expected to increase production through sustainable intensification. Increased production and mechanization, such as using combine harvesters leave farmers with more rice straw in the field, which farmers often choose to burn resulting in adverse health effects, increased air pollution and increased greenhouse gas emissions. Farmer adoption of recently promoted sustainable rice straw management practices is low. The present study, therefore, investigated factors influencing the acceptance of different rice straw management practices. 111 smallholder rice farmers participated in the study. Farmers’ perceptions of risks, benefits and their acceptance of eight different rice straw management practices including burning, soil incorporation, composting, mushroom and biogas production, and different collection methods, was investigated via a survey questionnaire. Results show that farmers often burn their rice straw even though they perceive high risks, few benefits and expressed low levels of acceptance for rice straw burning. Acceptance of rice straw management practices differs between practices; however, benefit perceptions are the strongest predictor for all practices followed by knowledge about climate change. Risk perceptions were a weak predictor for some practices including burning and biogas production. The regression models explain up to 50% of the variance. Results show that the experiential system determines farmers’ perception of practiced straw management options. This study also shows that even though climate change is not psychologically distant to farmers, sustainable behavior will depend on the acceptability, feasibility and perceived benefit of options provided.